Weak Alertness Between The Central Government and Local Governments in Handling Crisis. - Fita, Gia Ayu; Amiruddin, Ahmad; Saputra, Aco Nata (International Journal of Educational Research & Social Sciences, 2021)
At the end of 2019, the world is being hit by a pandemic worrying for humanity. Covid-19 first appeared in the city of Wuhan, China, and spread massively throughout the world afterwards. WHO has designated Covid-19 as a pandemic that is difficult to control as of March 11, 2020. As of April 2020, there have been more than 2 million cases of people in the world infected with Covid-19, and 195 thousand people died at that time. In Indonesia itself, the government has taken preventive measures to respond and prevent the virus's spread. The response of the government, especially local governments in Indonesia, is very diverse. Judging from the local government's readiness, some have responded slowly and underestimated this pandemic's emergence. Therefore, in this paper, the state's readiness, especially local governments, will be highlighted in facing a crisis (pandemic) from the aspects of risk, impact, and mitigation to the community itself.